Situation Report: Poland, 20 January 1989 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. PUWP Accepts the Prospect of Legalizing Solidarity / by Jan de Weydenthal Jaruzelski and Walesa Give Press Conferences / by Jan de Weydenthal Party Plenum Debates the Pros and Cons of Pluralism / by Louisa Vinton Polish-West German Relations on the Eve of Rakowski's Unofficial Visit to Bonn / by Anna Swidlicka Banned Polish Journalists' Association Presses for Relegalization / by Louisa Vinton A Profile of Stefan Bratkowski / by Anna Swidlicka